Cross-tongue procedure: a new treatment for long-standing numbness of the tongue. Issue 9 (November 2015) - Biglioli, Federico; Allevi, Fabiana; Colletti, Giacomo; Lozza, Alessandro
Abstract: The lingual nerve may be injured during oral procedures, usually during extraction of lower third molars. Patients often complain of numbness of the hemitongue postoperatively. If this persists for 3 months or more, microsurgical exploration and reconstruction of the lingual nerve is required, and better outcomes are achieved after early repair. After 18-24 months the production of axoplasmic fluid through the axons of the proximal stump is reduced, and neurorrhaphy between the proximal and distal stumps is not recommended. In such cases we suggest that a portion of the opposite lingual nerve should be used as an additional nerve source.